Why gender diversity in the boardroom affects firm performance: Insights from female directors - Lacerda, Teresa Correia de (Conferência - Investigação e Intervenção em Recursos Humanos, 2018)
Several empirical studies have emerged addressing Women on Corporate Boards (WOCB) and reporting a positive relationship between board gender diversity and better financial firm performance (Carter, Simkins, & Simpson, 2003; Erhardt, Werbel, & Shrader, 2003; Kang, Ding, & Charoenwong, 2010; Mahadeo, Soobaroyen, & Hanuman, 2011), showing how WOCB make a difference by influencing actual changes in board behavior such as board effectiveness (Huse, Nielsen, & Hagen, 2009), and finally indicating that WOCB improves corporate governance by using the whole talent pool available, and building more inclusive and diverse firms that reflect their stakeholders (Terjesen, Sealy, & Singh, 2009). Despite this increasing attention, not much consideration has been given to the female directors’ experience in the boardroom. If evidence shows that gender diversity on corporate boards contributes to more effective corporate governance, how can anyone identify the direct and indirect levels of influence? If women directors have a direct influence on the firm’s bottom line, what are the mechanisms used and how did the influential processes occur? These are some of the questions addressed by this study which aims to examine the direct outcomes of having more women on corporate boards and exploring how women contribute most effectively in their role as corporate board directors. Following a phenomenological approach, this study aims to understand a complex situation which is the role and experience of female directors in the corporate boardrooms. The fieldwork will consist of a qualitative study to provide the researcher with meaningful insights and enhance the understanding of female directors’ experience in the boardroom. Thus, the findings from the qualitative research that will be obtained through in-depth interviews to female directors will provide deep understanding of these phenomena which will help to characterize attitudes and behaviors of female directors. Therefore, this study contributes to the WOCB literature in a number of ways. First, the main contribution rests on the investigation of the role of female directors in enhancing the board effectiveness. Further, this study helps to explain the conditions under which a diverse board of directors is an effective device to increase financial firm performance. By analyzing board structure in a gender framework, this study extents previous findings about gender board diversity and its effects on firm performance. Finally, this study will bring additional insights on how WOCB impact their relationships with key stakeholders, and about their roles as leaders and mentors for other women serving as guidelines for other women pursuing directorship positions.